Determination Method of Excavation Damage Zone Based on Surrounding Rock Damage-Fracture Ratio in Underground Engineering - Guo, Haosen; Tong, Jiaqi; Sun, Qiancheng; Yang, Xu; Luo, Wenjun; Yu, Yang (Frontiers in Earth Science, 2022)
The depth of excavation damage zone in surrounding rock mass is an important parameter to determine the support design scheme, and also of great reference significance to evaluate the stability of surrounding rock. Acoustic test is the most commonly used method to obtain the depth of excavation damage zone in surrounding rock. However, under high stress condition, the surrounding rock is seriously broken and the internal structural planes are significantly developed, leading to the test error reaching meter-level. This paper, based on dimensional analysis, proposed the surrounding rock damage-fracture ratio R to characterize the relationship between excavation damage zone and highly damaged zone. The established indicator, considered the stress condition of engineering zone, rock integrity, tunnel excavation span and rock fracture zone depth, was verified with allowable error in engineering practice. The results show that the model can overcome the limitations of acoustic wave testing method in surrounding rock testing of deep underground cavern, and the method of determining the depth of surrounding rock damage zone based on the damage-fracture ratio R provides a practical and alternative method for determining the damage zone of surrounding rock excavation.